The Role of Neutrophil NETosis in Organ Injury: Novel Inflammatory Cell Death Mechanisms - Cahilog, Zhen (Inflammation, 2020)
NETosis is a type of regulated cell death dependent on the formation of neutrophil extracellular traps (NET), where net-like structures of decondensed chromatin and proteases are produced by polymorphonuclear (PMN) granulocytes. These structures immobilise pathogens and restrict them with antimicrobial molecules, thus preventing their spread. Whilst NETs possess a fundamental anti-microbial function within the innate immune system under physiological circumstances, increasing evidence also indicates that NETosis occurs in the pathogenic process of other disease type, including but not limited to atherosclerosis, airway inflammation, Alzheimer’s and stroke. Here, we reviewed the role of NETosis in the development of organ injury, including injury to the brain, lung, heart, kidney, musculoskeletal system, gut and reproductive system, whilst therapeutic agents in blocking injuries induced by NETosis in its primitive stages were also discussed. This review provides novel insights into the involvement of NETosis in different organ injuries, and whilst potential therapeutic measures targeting NETosis remain a largely unexplored area, these warrant further investigation.